Perbandingan Sektor Unggulan Perekonomian Kota Banda Aceh (Periode 2012-2016) - Isthafan Najmi (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
The number of people continues to grow means economic needs are also increasing, so it needs additional revenue every year. This can be achieved by increasing the aggregate output (goods and services) or Gross Regional Domestic Product every year. This study aims to determine the comparison of the leading economic sectors of Banda Aceh City as an information and consideration in the planning of economic development. Using secondary data in the form of Gross Regional Domestic Product of Banda Aceh City Period 2012-2016. The analytical tools used are Location Quotient (LQ) analysis, Shift Share Analysis. Location Quotient analysis results show that the calculation of Shift-Share Gross Regional Domestic Product of Banda Aceh without Oil and Gas Regency during the period of 2012-2016 shows that the value of Proportional Shift (P) there is a positive value of Mining and Quarrying and Agriculture, Forestry and Fisheries, while for the sector - sectors with negative Proportional Shift (P) values have one sector, namely Processing Industry. The sectors are categorized as the basic sector in the economy of Banda Aceh City which has LQ> 1 value ranging from the largest is the service sector of the company and the water supply sector, waste management, waste and recycling. The sectors are categorized as non-base sector because it has LQ <1 value ie agriculture, forestry and fishery.